2014
DOI: 10.1073/pnas.1319848111
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive structural model of the mechanochemical cycle of a mitotic motor highlights molecular adaptations in the kinesin family

Abstract: Kinesins are responsible for a wide variety of microtubule-based, ATP-dependent functions. Their motor domain drives these activities, but the molecular adaptations that specify these diverse and essential cellular activities are poorly understood. It has been assumed that the first identified kinesin-the transport motor kinesin-1-is the mechanistic paradigm for the entire superfamily, but accumulating evidence suggests otherwise. To address the deficits in our understanding of the molecular basis of functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
78
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 38 publications
10
78
0
Order By: Relevance
“…For example, does the partial NL docking implied by phosphate sensitivity represent a distinct structural state-and therefore a mechanical substepor a shift in some rapid equilibrium between fully docked and undocked conformations? Cryoelectron microscope structural studies of Eg5, a mitotic kinesin-5, have found hydrolysis-induced shifts in the NL conformation (36,37), and similar shifts may take place in kinesin-1. Moreover, previous work characterizing the motility of Eg5 has shown that its processivity can be also be enhanced by the addition of P i (38), suggesting that the P i release gating mechanism proposed here may not be limited to kinesin-1 motors.…”
Section: Discussionmentioning
confidence: 85%
“…For example, does the partial NL docking implied by phosphate sensitivity represent a distinct structural state-and therefore a mechanical substepor a shift in some rapid equilibrium between fully docked and undocked conformations? Cryoelectron microscope structural studies of Eg5, a mitotic kinesin-5, have found hydrolysis-induced shifts in the NL conformation (36,37), and similar shifts may take place in kinesin-1. Moreover, previous work characterizing the motility of Eg5 has shown that its processivity can be also be enhanced by the addition of P i (38), suggesting that the P i release gating mechanism proposed here may not be limited to kinesin-1 motors.…”
Section: Discussionmentioning
confidence: 85%
“…1B for Eg5. These labeling sites were selected based on prior structural studies (2,6,7,(9)(10)(11)(12)(17)(18)(19) to detect changes in the distance between the NL or switch-1 and relatively fixed locations in Ī²1 and Ī²7 by using time-resolved FRET between a fluorescent donor (AEDANS) and a nonfluorescent acceptor (DDPM) (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…The NL has been proposed to isomerize between two conformations: one that is flexible and termed undocked, and the other that is ordered and termed docked, where it interacts with a cleft in the motor domain formed by the twisted Ī²-sheet and is oriented along the MT axis (5-7). NL isomerization (5,8) is hypothesized to be the force-generating transition in kinesin motors (6,7,(9)(10)(11), and its position has also been proposed to coordinate the ATPase cycles of processive kinesin dimers by regulating nucleotide binding and hydrolysis (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Eg5 is roughly 10-fold slower than kinesin-1, although how this speed relates to the motor's processivity and force-generating ability is unclear. From CryoEM reconstructions, the Eg5 neck linker domain adopts a rearwardfacing orientation in the ADP state, in contrast to the more disordered kinesin-1 (9,10), although recent structural kinetics data identifies discrete neck linker positions in both motor classes (11). Eg5 has an extended Loop 5, which has been shown to affect nucleotide binding and serve as a latch for structural coupling within the Switch I domain (12,13) and as a binding target of several potential drugs (14 -16).…”
mentioning
confidence: 99%